MAKANAN ADAT PADA ACARA MAULID NABI DI KECAMATAN PADANG SAGO KABUPATEN PADANG PARIAMAN - Safitri, Mira; Yulastri, Asmar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The purpose research to describe about customary food of the Prophet’s birthday at Padang Sago of Padang Pariaman. This type of research is a descriptive qualitative method, at Padang Sago. Research object is the stages of the event is customary food of Prophet’s birthday. Data collection technique: observation, interview and documentation. Data analysis techniques include: data reduction,data display,conclusion and verification. The result showed (1)Stage of Prophet’s birthday of manyonsong, manduobaleh, and mahanta. (2)Customary types of food being served is confectionary and staple food. (3)The equipment used is dulang kanso,rumah kue, jamba nasi/senggan, rumah samba,rantang, plate, rice bowl, oval plate, food cover, kain rendo dan kain dalamak. (4)How the presentation using dulang kanso, rumah kue for confectionary, rice with jamba nasi/senggan, and side dishes with rumah samba. Ordinances meal is sitting on the floor eating food around the appropriate manners. (5)Meaning of indigenous food at the event about relationship among moeslims, social life and imitate nature Prophet.Keyword : Food customs, Padang Pariaman, Prophet’s birthday, Traditional event